Masjid Sebagai Ruang Kontemplasi: Menemukan Kedamaian di Tengah Kesibukan - Azzahra Kamila Cahyani Masdar; Nuradillah Nuradillah; Bayu Sagara; Fardan Ardinata; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The role of the mosque as a space for contemplation amidst the busy urban life. Mosques do not only serve as places of ritual worship, but also as spaces for spiritual reflection that help Muslims find inner peace. The simple and calming architecture and layout of the mosque provide a spiritual atmosphere that supports contemplation and mental tranquility. The purpose of this research is to explain the role of the mosque as a place of contemplation for individuals seeking peace amidst the activities and pressures of daily life. This research uses a literature review method with a tahlili interpretation approach to analyze relevant sources from the past 8 years. The research results prove that the main factors helping individuals achieve inner peace are practices such as dhikr, congregational prayers, and a solemn atmosphere during prayers. Spiritual activities in the mosque provide an opportunity for congregants to momentarily detach from worldly pressures and focus on their relationship with Allah, which significantly enhances their sense of peace and tranquility.